Assessment of the Operational Characteristics of Research Ethics Committees in Ghana. (February 2022) - Owusu, Samuel Asiedu; Addison, Grace; Redman, Barbara; Kearns, Lisa; Amuna, Paul; Laar, Amos
There were eighteen Research Ethics Committees (RECs) operating in Ghana as of December 2019 but no empirical assessment of their operational characteristics had been conducted. We assessed the characteristics of Ghanaian RECs using an existing Self-Assessment Tool for RECs in Developing Countries. We present results from nine RECs that participated in this nation-wide assessment. Our results indicate that the RECs are generally adherent to the recommendations in the Tool including being composed of members with diverse expertise. They also reviewed and approved research protocols as well as had access to some limited funding for their activities. There is no national policy on research human protections or an ethics authority to regulate the activities of the RECs. We recommend the establishment of this authority in Ghana while encouraging institutions to sustain efforts aimed at making their RECs operate independently.